TINJAUAN YURIDIS KEDUDUKAN BENDA JAMINAN HAK TANGGUNGAN KEPADA BANK YANG TERKAIT KASUS KORUPSI - YENNY YUSTISI YANTI (PREMISE LAW JURNAL, 2015)
Immovable properties such as land and buildings which are bound in hypothecation give the privilege to preferred creditor as the receiver of the hypothecation to execute the collateral when debtors are not able to pay off their debts. The research used judicial normative method. The confiscation of the collateral by the Court can be opposed by the third party that believed to be harmed and is contradictory to the principle of legal protection for preferred creditor because every movable and immovable property which has been mortgaged cannot be confiscated since it has been the authority of the creditor as the receiver of the collateral. A creditor who has bound in the collateral with good faith must be legally protected, and every immovable property such as land and building which been bound in collateral becomes the full authority of the creditor as the mortgagee as the security from the debtor as the mortgagor. Keywords: Hypothecation, Bank, Confiscation, Criminal Act, Corruption